An application of Kano method in the elicitation of stakeholder satisfying requirements for an e-Ebola awareness system - Hussain, Azham; Mkpojiogu, Emmanuel O.C. (North Atlantic University Union, 2016)
Several software requirements elicitation techniques exist and are used in the elicitation of software requirements.However, most of the techniques are limited in that they are only effective in capturing the voice of the customer/user.They are not effective in capturing their mind.There are some kinds of requirements that stakeholders take for granted, not expecting or are not apt to voice out.Such requirements need special requirements elicitation approaches that will probe the psychology of the respondents so as to succinctly collect the needed requirements from them were necessary.Kano model provides a framework that enables the elicitation of these kinds of requirements.More so, it allows appropriate requirements to be elicited that will lead to the satisfaction of stakeholders if the requirements are met or to their dissatisfaction if they are unmet.It categorizes software requirements based on some quality attributes that describes the kind of requirements elicited. The Kano approach also, helps to obtain the perceived quality of the proposed product from the customer/users’ point of view.This method helps to filter out requirements that do not lead to the satisfaction of stakeholders and thus the quality of elicited requirements and the proposed software solution.Kano method, though popular in the interdisciplinary field of quality management, is seldom applied in the field of software engineering, especially in requirements elicitation. In this study, the Kano method was applied in the elicitation of requirements for a proposed e-Ebola Awareness System.The result of the Kano analysis indicated that the elicitation of stakeholders’ satisfying requirements leads to increase in the satisfaction level of potential users/customers of the would-be product.It also indicated improvement in the perceived quality of such product from the viewpoint of the potential users/customers as shown from the customer satisfaction coefficients and the self-stated importance ratings.